CRYSTAL STRUCTURE OF MAHNERTITE - Pushcharovsky D.Yu.; Zubkova N.V.; Teat S.J.; MacLean E.J.; Sarp H. (My University, 2004)
Mahnertite, (Na0.88Ca0.12)Cu-2.75[AsO4](2)Cl-0.62.3.63H(2)O, M = 565.17, is tetragonal, with space group I4/mmm, a = 10.037(1), c = 23.739(1) Angstrom, V = 2391.5(4) Angstrom(3), Z = 8, rho(o) = 3.32, rho(c) = 3.14 g/cm(3), mu 9.78 mm(-1). The crystal structure of mahnertite was solved and refined against data collected at the Daresbury Synchrotron Radiation Source, using a 20 x 20 x 2 mum(3) single crystal, lambda = 0.6898 Angstrom, F(000) = 2150, R = 0.049 for 639 reflections with I > 2sigma(I). The structure consists of sheets parallel to (001), which comprise two symmetrically independent distorted Cu 5-vertex square pyramids Cuphi5 (phi = O, Cl or H2O) as well as AsO4 tetrahedra. Four Cuphi(5) pyramids located around the 4-fold axis share edges to form clusters linked by AsO4 tetrahedra. The sheets are linked by the common apical vertex of the Cu(2)phi(5) polyhedra. As a result, a heterogeneous framework is formed. (Na,Ca) atoms, additional Cu(3) cations and H2O molecules are located in the interlayers. The mineral is structurally related to zdenekite, NaPbCu5(AsO4)(4)Cl.5H(2)O.
Keywords: Mahnertite